Investigating the Neuroprotective Effect of Alcholic Extracts of Achillea Biebersteinii Leave on α Motoneurons after Sciatic Nerve Compression in Rats - M Alikhanzade; M Tehranipour; J Khayatzade (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2014)
Introduction: The effects of injuries in peripheral nervous system returns to the cell body of neurons in central nervous system in a retrograde manner which leads to brain and spinal degeneration. It is probable that Achillea biebersteinii might prevent the injury progress. Hence, the present study aimed to investigate the neuroprotective effect of alcholic extract of Achillea biebersteinii leaves on spinal α motoneurons degenarion after sciatic nerve compression in rats. Methods: 30 male wistar rats were divided randomly into groups of control, compression, compression with treatment of 50, 75, 100 mg/kg doses. Sciatic nerve was exposed to compression for 60 s using locker pincers. Extract injection was done intraperitoneally in the first and second weeks after compression. Then 28 days after compression under perfusion method, the lumber spinal cord was sampled. After cutting and coloring, the density of motoneurons was measured using dissector methods. Results: The study results demonstrated a meaningful difference between compression and control groups in regard with neuronal density (P=0.000). Neuronal density showed also a significant meaningful increase (P<0.01) in alcoholic extract treatment groups of 50,75,100 mg/kg compared to the compression group. Conclusion: The study findings revealed that Alcohlic extracts of Achillea biebersteinii leaves, containing growth and regeneration factors, has neuroprotective effect on spinal cord alpha motoneurons after injury. The extract with 75mg/kg dose was reported as the most effective one.